The World in two round Trips - Schurmann, David (Brazil, 2007)
"The World in Two Round Trips" tells the story of the Schürmann Family as they sail around the world retracing the voyage of Ferdinand Magellan. Part travelogue, part family adventure, the film features lush footage from 19 different nations.
Verzio Film Festival Submission
Keywords: Documentary films